Epidemiology and forensic Science (Research, Society and Development, 2022)
Forensic Epidemiology unites the principles and techniques of epidemiology and forensic sciences and makes it possible to fill gaps between legal issues involving clinical (health-disease) and epidemiological situations, establishing the causal link in civil actions and criminal and defense proceedings. The aim of this paper was to provide a brief overview of the methods and applications of forensic epidemiology, as forensic epidemiology is of interest to those who work and study in the fields of forensic medicine, epidemiology and law. This is a qualitative, descriptive, narrative review of the literature. The bibliographic search was carried out in the databases. Scielo, Google Scholar, since the late 1990s, when the term forensic epidemiology was coined. As a result, situations related to the applications of forensic epidemiology were generated, such as areas of Forensic Toxicology; Benefits (sick pay and disability retirement); Suicide; Traffic accidents and alcohol; Domestic violence; Infanticide. This study had limitations, among them the search for articles in Portuguese, with the scope focused on forensic epidemiology itself. However, we can highlight that this study showed the importance of investigating this topic and it is necessary to expand research both nationally and internationally.